Tissue engineering for human urethral reconstruction: systematic review of recent literature. - Vincent de Kemp; Petra de Graaf; Joost O Fledderus; J L H Ruud Bosch; Laetitia M O de Kort (PLoS ONE)
Background Techniques to treat urethral stricture and hypospadias are restricted, as substitution of the unhealthy urethra with tissue from other origins (skin, bladder or buccal mucosa) has some limitations. Therefore, alternative sources of tissue for use in urethral reconstructions are considered, such as ex vivo engineered constructs. Purpose To review recent literature on tissue engineering for human urethral reconstruction. Methods A search was made in the PubMed and Embase databases restricted to the last 25 years and the English language. Results A total of 45 articles were selected describing the use of tissue engineering in urethral reconstruction. The results are discussed in four groups: autologous cell cultures, matrices/scaffolds, cell-seeded scaffolds, and clinical results of urethral reconstructions using these materials. Different progenitor cells were used, isolated from either urine or adipose tissue, but slightly better results were obtained with in vitro expansion of urothelial cells from bladder washings, tissue biopsies from the bladder (urothelium) or the oral cavity (buccal mucosa). Compared with a synthetic scaffold, a biological scaffold has the advantage of bioactive extracellular matrix proteins on its surface. When applied clinically, a non-seeded matrix only seems suited for use as an onlay graft. When a tubularized substitution is the aim, a cell-seeded construct seems more beneficial. Conclusions Considerable experience is available with tissue engineering of urethral tissue in vitro, produced with cells of different origin. Clinical and in vivo experiments show promising results.